Simultaneous administration of high-dose atorvastatin and clopidogrel does not interfere with platelet inhibition during percutaneous coronary intervention - Kreutz RP; Breall JA; Sinha A; von der Lohe E; Kovacs RJ; Flockhart DA (Dove Medical Press, 2016)
Rolf P Kreutz,1,2 Jeffrey A Breall,1 Anjan Sinha,1 Elisabeth von der Lohe,1 Richard J Kovacs,1 David A Flockhart,2,† 1Krannert Institute of Cardiology, 2Division of Clinical Pharmacology, Indiana University School of Medicine, Indianapolis, IN, USA †David A Flockhart passed away on November 26, 2015 Background: Reloading with high-dose atorvastatin shortly before percutaneous coronary interventions (PCIs) has been proposed as a strategy to reduce periprocedural myonecrosis. There has been a concern that statins that are metabolized by cytochrome P450 3A4 may interfere with clopidogrel metabolism at high doses. The impact of simultaneous administration of high doses of atorvastatin and clopidogrel on the efficacy of platelet inhibition has not been established. Methods: Subjects (n=60) were randomized to receive atorvastatin 80 mg together with clopidogrel 600 mg loading dose (n=28) versus clopidogrel 600 mg alone (n=32) at the time of PCI. Platelet aggregation was measured at baseline, 4 hours after clopidogrel loading dose, and 16–24 hours after clopidogrel loading dose by light transmittance aggregometry using adenosine diphosphate as agonist. Results: Platelet aggregation was similar at baseline in both the atorvastatin and the control groups (adenosine diphosphate 10 µM: 57%±19% vs 61%±21%; P=0.52). There was no significant difference in platelet aggregation between the atorvastatin and the control groups at 4 hours (37%±18% vs 39%±21%; P=0.72) and 16–24 hours post-clopidogrel loading dose (35%±17% vs 37%±18%; P=0.75). No significant difference in incidence of periprocedural myonecrosis was observed between the atorvastatin and control groups (odds ratio: 1.02; 95% confidence interval 0.37–2.8). Conclusion: High-dose atorvastatin given simultaneously with clopidogrel loading dose at the time of PCI does not significantly alter platelet inhibition by clopidogrel. Statin reloading with high doses of atorvastatin at the time of PCI appears to be safe without adverse effects on platelet inhibition by clopidogrel (ClinicalTrials.gov: NCT00979940). Keywords: clopidogrel, atorvastatin, myocardial infarction, percutaneous coronary intervention, platelet aggregation